TINJAUAN YURIDIS TENTANG PENYELESAIAN SENGKETA HARTA WARIS MELALUI PERDAMAIAN - Oppy Tri Oktarini (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTIndonesian inheritance law is still pluralistic in nature, meaning that there is no unified inheritance law that can be applied comprehensively to Indonesian society. Inheritance law in Indonesia currently applies three systems of inheritance law, namely Islamic inheritance law, civil inheritance law, customary inheritance law. Of the three legal systems that regulate inheritance, of course, they have different sources of law from one another. Inheritance is a method of settling legal relations in society, which creates more or fewer difficulties due to the death of a person. In general, this study aims to determine the legal rules regarding the distribution of inheritance according to KHI, and the procedure for settling inheritance disputes through peace. This research method used is normative juridical. This conclusion shows that the law of inheritance in the compilation of Islamic law (KHI) article 171 point (a) is: the law that regulates the transfer of ownership of inheritance (tirkah) heirs, determines who has the right to become heirs and how much of each.Keywords: Inheritance, Peace